The Influence of Socioeconomic Factors on Kentucky's Public School Accountability System:Does Poverty Impact School Effectiveness? - Lyons, Robert (Education Policy Analysis Archives, 2004)
Under the Commonwealth Accountability Testing System (CATS), Kentucky's public schools have been assigned individualized baseline and improvement goal indices based upon past school performance in relation to the 2014 statewide index goal of 100. Each school's CATS Accountability Index, a measure of school performance based upon both cognitive and non-cognitivemeasures, has then been compared to these individualized improvement goals for the purpose of designating schools as Meet Goal, Progressing, and Assistance Level (Kentucky Department of Education (KDE), 2000). Considered an interim target model, the design of CATS has been intended to negate the biasing effects of socioeconomic factors on school performance on accountability tests through the individualization of school goals (Ladd. 2001). Results of this study showed that 39.9% to 55.5% of the variance of the CATS indices was shared by school socioeconomic factors. Analysis of this interim target model for the 2000-2002 biennium showed that for elementary and middle schools this model negated the biasing effects of socioeconomic factors, but not for high schools. Moreover, analysis of the progress of schools toward their Improvement Goals in 2001 showed that both elementary and high schools from higher poverty backgrounds lagged significantly behind their more affluent peers, indicating inequitable capacity to meet improvement goals between the poorest and most wealthy schools. Adaptations to the present accountability systems were suggested for the purpose of providing more accurate information to the public regarding the effectiveness of public schools in Kentucky.